Analisis Kelayakan Struktur Bangunan SDN 22 Talamau Pasca Gempa Pasaman Barat - Wati, Zuly Nelriska; Masdar, Astuti; Rahmad, Anda (Jurnal Bangunan, Konstruksi & Desain, 2025)
The West Pasaman earthquake on February 25, 2022, with a magnitude of 6.2, caused damage to various buildings, including the educational facility of SDN 22 Talamau. As a public facility used by children, the school building requires immediate evaluation to ensure its safety and suitability. This study aims to analyze the structural suitability of SDN 22 Talamau after the earthquake using visual assessment methods, hammer tests, and structural modeling with SAP2000 version 14 software. The results showed that the building suffered damage to both structural and non-structural elements. The damage was relatively minor, such as hairline cracks in the walls, peeling plaster, and minor damage to columns and beams, making it repairable. With repairs to the column-beam connections and wall repairs using injection or wire mesh methods, the building was declared still suitable for use. Recommendations for repairs were provided to ensure the safety and functionality of the building in the future.